Effectiveness of the process of preparing for patients before laparoscopic colectomy surgery due to cancer - Xuan, Nguyen Thanh; Ly, Nguyen Thi Thanh; Anh, Nguyen Thi Kim; Huong, Nguyen Thi Mai; Thao, Nguyen Thanh Phuong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Purpose: To build and assess the result of the implementation in the Mechanical Bowel Preparation (MBP) process for patients undergoing laparoscopic elective colorectal surgery for cancer at the General Surgery Department in the International Medical Centre of Hue Centre Hospital. Method: 41 colorectal cancer patients had laparoscopic elective surgery from 01/2019 to 03/2020. To observe the performance of the preoperative preparation process for patients undergoing elective surgery and assess the effectiveness of treatment, the complication rate such as anastomotic leak, wound infection, and intra - abdominal abscess. Patients were followed up for 30 days after operation. Results: 100% of patients completed the process, and the complication rate of anastomotic leak was 0%. Wound infection occupied 14,6%, including 6 patients; intra-abdominal abscess occupied 2,4%, including 1 patient; and early postoperative adhesive small bowel obstruction occupied 0%. Conclusion: Non - mechanical bowel Preparation (MBP) reduces the amount of work for nurses, creates a good spirit for the patient before the operation, and doesn’t increase the complication rate.